The Effect Of Size Company, Profitability, Financial Leverage and Dividend Payout Ratio on Income Smoothing in The Manufacturing Companies Listed in Indonesia Stock Exchange Period 2010-2013 - Yunus Fiscal; Agatha Steviany (Jurnal Akuntansi dan Keuangan, 2015)
This study aims to identify and analyze the effect of firm size, profitability, financial leverage,and dividend payout ratio on income smoothing in the manufacturing companies listed in Indonesia Stock Exchange period 2010-2013. The first hypothesis is firm size has positive effect on income smoothing, the second hypothesis is profitability has positive effect on income smoothing, the third hypothesis is financial leverage has positive effect on income smoothing, and the fourth hypothesis is dividend payout ratio has positive effect on income smoothing. Measurement of income smoothing is based on the Eckel Index. The sample in this study is manufacturing companies that listed in Indonesia Stock Exchange period 2010-2013. Sampling using purposive sampling in order to obtain a total sample of 27 manufacturing companies that meet the criteria of the study sample set. Company size is measured by total assets, profitability measured by Net Profit Margin (NPM), financial leverage measured by Debt to Equity Ratio (DER), and Dividend Payout Ratio. The technique of data analysis done with the binary logistic regression analysis using SPSS 18.0 for windows. The results showed that in firm size, profitability, and financial leverage has positive effect on income smoothing in the manufacturing companies are listed in the Indonesia Stock Exchange, while the variable dividend payout ratio does not have effect on income smoothing in the manufacturing companies are listed in the Indonesia Stock Exchange.